Model Pengaruh Tingkat Suku Bunga Terhadap Kurs Rupiah - Elinora Naikteas Bano; Nina Valentika (Fakultas Pertanian, Universitas Timor, 2022)
This study examines the effect of interest rates on the rupiah exchange rate. The method used in this research is simple linear regression analysis. This study found that interest rates have a significant positive effect on the rupiah exchange rate of 1.804704 at a 5% level of significance.